Differences in dominant and non-dominant leg hamstring-to-quadrizeps ratio at a 60°/s in division I college male golfers - Durbin, K.; Sun, D.; Franklin, W.; Smith, D. B. (International Journal of Exercise Science Conference Proceedings, 2024)
During the golf backswing players shift their weight back towards the plant leg, pause briefly then rapidly shift their weight forward towards the front leg while preparing the club for impact with the ball. Lower body strength contributes not only to postural balance while performing a swing but also to power generation. For most people the golf swing appears simple, but in reality there are a lot of muscles activated from the feet to the hands and injuries can occur along the way.